CRISPR-Cas9 Multiplex Editing of the α-Amylase/Trypsin Inhibitor Genes to Reduce Allergen Proteins in Durum Wheat - Camerlengo, Francesco; Frittelli, Arianna; Sparks, Caroline; Doherty, Angela; Martignago, Damiano; Larré, Colette; Lupi, Roberta; Sestili, Francesco; Masci, Stefania (Frontiers in Sustainable Food Systems, 2020)
Wheat and its derived foods are widespread, representing one of the main food sources globally. During the last decades, the incidence of disorders related to wheat has become a global issue for the human population, probably linked to the spread of wheat-derived foods. It has been ascertained that structural and metabolic proteins, like α-amylase/trypsin inhibitors (ATI), are involved in the onset of wheat allergies (bakers' asthma) and probably Non-Coeliac Wheat Sensitivity (NCWS). The ATI are a group of exogenous protease inhibitors, which are encoded by a multigene family dispersed over several chromosomes in durum and bread wheat. WTAI-CM3 and WTAI-CM16 subunits are considered among the main proteins involved in the onset of bakers' asthma and probably NCWS. A CRISPR-Cas9 multiplexing strategy was used to edit the ATI subunits WTAI-CM3 and WTAI-CM16 in the grain of the Italian durum wheat cultivar Svevo with the aim to produce wheat lines with reduced amount of potential allergens involved in adverse reactions. Using a marker gene-free approach, whereby plants are regenerated without selection agents, homozygous mutant plants without the presence of CRISPR vectors were obtained directly from T0 generation. This study demonstrates the capability of CRISPR technology to knock out immunogenic proteins in a reduced time compared to conventional breeding programmes. The editing of the two target genes was confirmed either at molecular (sequencing and gene expression study) or biochemical (immunologic test) level. Noteworthy, as a pleiotropic effect, is the activation of the ATI 0.28 pseudogene in the edited lines.